АДАПТЕРНИЙ ПРОТЕЇН Ruk/CIN85 РЕГУЛЮЄ РЕДОКС-БАЛАНС У КЛІТИНАХ РАКУ ГРУДНОЇ ЗАЛОЗИ МИШІ ЛІНІЇ 4Т1 - Horak, I.R.; Latyshko, N.V.; Hudkova, O.O.; Tokarchuk, K.O.; Kishko, T.O.; Yusova, O.I.; Drobot, L.B.; Tykhomyrov, A.A. (PH Akademperiodyka, 2023)
Background: Cell surface plasmin is involved in tumor growth and metastatic dissemination by regulating cancer cells adhesion, migration and invasion. Plasmin-induced cell detachment is accompanied by an increased rate of reactive oxygen species (ROS) generation and cell death. However, cancer cells acquire the ability to develop adaptive mechanisms to resist ROS-mediated apoptosis. Aim: To establish the role of adaptor protein Ruk/CIN85 in the control of viability and redox balance in breast adenocarcinoma cells exposed to plasmin(ogen). Materials and Methods: Mouse 4T1 cells with the stable overexpression of adaptor protein Ruk/CIN85 (RukUp subline) and corresponding control (Mock subline) were treated with Glu-plasminogen (1–100 nM). Plasminogen to plasmin conversion was monitored spectrophotometrically by cleavage of the specific chromogenic substrate S2251. Specific uPA inhibitor BC11 was used to verify the uPA-mediated mechanism of plasminogen pericellular activation by 4T1 cells. Cell survival rate was assessed by MTT-test and cell proliferation was estimated by colony formation assay. Enzymatic activities of catalase, glutathione peroxidase, superoxide dismutase, as well as hydrogen peroxide (H2O2) levels were measured by spectrophotomertric and fluorometric assays. The intracellular ROS generation was monitored by flow cytometry using H2DCF-DA fluorescent probe. Results: Plasminogen was shown to be converted into an active proteinase plasmin on the surface of carcinoma cells in uPA-dependent manner. Plasmin(ogen) suppressed proliferation and affected survival of both studied 4T1 sublines. However, RukUp cells displayed higher resistance to plasmin(ogen)-induced cytotoxicity than Mock cells. Plasmin(ogen) promoted significant elevation in ROS generation rate in cells with the basal level of Ruk/CIN85 expression. In contrast, RukUp cells appear to be more effective in counteracting prooxidant changes due to the activation of some enzymes of the glutathione system, in particular glutathione peroxidase, and a concomitant decrease of H2O2 accumulation. Conclusion: Adaptor protein Ruk/CIN85 is involved in the regulation of redox homeostasis in cancer cells to maintain levels of ROS, thus promoting redox adaptation in cancer cells exposed to plasmin(ogen). Thus, Ruk/CIN85 may represent one of the relevant targets in order to diminish the resistance of cancer cells to ROS-mediated apoptosis.